Penerapan Evidence Based Practice Pemberian Tepid Water Sponge pada Anak dengan Dengue Hemoragic Fever dengan Masalah Keperawatan Hipertermia - Porajow, Mevlin; Kairupan, Michelle (JURNAL ILMIAH KESEHATAN MANADO, 2025)
Giving Water Tepid Sponge can be used to reduce hyperthermia by increasing the evaporation process through the skin. Giving Water Tepid Sponge can also provide comfort, reduce pain and anxiety. Objective: To determine the administration of Water Tepid Sponge to reduce hyperthermia in pediatric patients with Dengue Hemorrhagic Fever (DHF). This research method uses a case study method with a Nursing Care approach by taking one case as the unit of analysis. The unit of analysis is a child client with hyperthermia with the intervention of giving Water Tepid Sponge for 60 minutes to a child patient with Dengue Hemorrhagic Fever (DHF). The results of this study show that giving Water Tepid Sponge can reduce hyperthermia in pediatric patients with Dengue Hemorrhagic Fever (DHF) as much as after 60 minutes of treatment. Water Tepid Sponge can reduce hyperthermia in pediatric patients with Dengue Hemorrhagic Fever (DHF),